PENERAPAN ANGLE CAMERA DALAM VIDEOGRAFI JURNALISTIK SEBAGAI PENYAMPAI BERITA DI METRO TV BIRO MEDAN - Christian Pangihutan Sitorus; Besti Rohana Simbolon (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2019)
Camera angle in photography and videography is very decisive in the delivery of messages and information that will be presented. In video recording or shooting, there are often cases or wrong angle incidents in coverage by cameramen. Where wrong angle events can cause different perceptions and opinions from viewers who are not directly proportional to the information that the television station wants to convey or broadcast. The angle error there are cameras that have a big impact and there are also small ones that are not so influential but still interfere in the process of shooting rules let alone in covering journalistic news. 80 percent of the use of detail is closeup, extreme closeup, and medium closeup. 20 percent only use wide angle like Longshot and Mediumshot. General also uses angle eye level, high angle, low angle, bird eye view, and frog eye. And in terms of factors which inhibits the nature of our application angle era is the lack of practice and understanding, lack of information seeking from professional media, and difficulty in placing motivation of the script with the angle to be used.